2012
DOI: 10.1210/me.2012-1199
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA (miR)-199a/214 Cluster Mediates Opposing Effects of Progesterone and Estrogen on Uterine Contractility during Pregnancy and Labor

Abstract: Progesterone (P(4)) and estradiol-17β (E(2)) play critical and opposing roles in regulating myometrial quiescence and contractility during pregnancy and labor. Although these contrasting hormonal effects are likely mediated via differential regulation of inflammatory and contractile genes, the underlying mechanisms remain incompletely understood. Recently we discovered that targets of the microRNA (miR)-200 family, transcription factors zinc finger E-box binding homeobox (ZEB)-1 and ZEB2, serve as P(4)/progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 55 publications
2
77
0
Order By: Relevance
“…More recently, miRNAs have been implicated in hormone responsiveness and the regulation of key gene expression pathways involved in parturition [58]. Enquobahrie et al reported a distinct group of miRNAs, such as hsa-miR-199a-3p, -202-5p, and -214-3p, differentially expressed in human fetal membranes in term labouring samples [59].…”
Section: Mirna Regulationmentioning
confidence: 99%
“…More recently, miRNAs have been implicated in hormone responsiveness and the regulation of key gene expression pathways involved in parturition [58]. Enquobahrie et al reported a distinct group of miRNAs, such as hsa-miR-199a-3p, -202-5p, and -214-3p, differentially expressed in human fetal membranes in term labouring samples [59].…”
Section: Mirna Regulationmentioning
confidence: 99%
“…We are only beginning to discover the roles of miRNAs in reproduction. miRNAs have been implicated in endometrial receptivity, [34][35][36] implantation, 37-42 labor [43][44][45][46][47] and even spontaneous fetal loss in the pig. 48,49 In the uterus, most of the physiological changes occurring over the estrous/menstrual cycle and during pregnancy are driven by the ovarian hormones.…”
Section: Microrna Regulation In the Uterusmentioning
confidence: 99%
“…As noted, the expression of COX-2 increases in the pregnant myometrium during late gestation and is believed to be critical for the increase in contractile PGF 2 a required for the progression to labor. Our studies revealed that COX-2 also is a bona fide target of miR-214 (Williams et al 2012b). In pregnant mouse myometrium, Cox-2 protein levels were significantly increased at 18.5 dpc and during labor, compared with 15.5 dpc, as miR-199a-3p and miR-214 reciprocally declined.…”
Section: Other Mechanisms For the Decline In Pr Function Leading To Pmentioning
confidence: 59%
“…Estrogens induce an influx of macrophages and neutrophils into the uterus and antagonize the anti-inflammatory actions of P 4 / PR (Tibbetts et al 1999;Mesiano et al 2002). ERa activation also promotes labor by enhancing transcription of genes for OXTR (Murata et al 2003), CX43 (Piersanti and Lye 1995) and COX-2 (Mesiano et al 2002;Williams et al 2012b), which is expressed at low to undetectable levels in the uterus throughout most of pregnancy, but is highly up-regulated at term (Tsuboi et al 2000;Engstrom 2001;Williams et al 2012b). MicroRNAs that were significantly down-regulated near term in our microarray analysis included miR-199a-3p, known to target COX-2 mRNA (Chakrabarty et al 2007) and miR-214, which targets PTEN and activates the Akt pathway Yin et al 2010).…”
Section: Other Mechanisms For the Decline In Pr Function Leading To Pmentioning
confidence: 99%